Exploring parent-child relationships of Malay-female adolescents who had engaged in pre-marital sex - Ahmad Sudan, Salmi; Ismail, Nik Ahmad Hisham; Ssekamanya, Siraje Abdallah (Institut Terjemahan dan Buku Malaysia, 2016)
Increasing incidence of out of wedlock and unwanted pregnancies which result in the abandonment and killing of innocent babies. Problems and challenges the adolescent females especially those without family support.